AKUNTABILITAS DAN TRANSPARANSI PENGADAAN KAPAL NELAYAN PADA PROGRAM PENGELOLAAN PERIKANAN TANGKAP DI KEMENTERIAN KELAUTAN DAN PERIKANAN - Suyanti, - (2019)
This research is an interpretive ethnometodology qualitative study which aims to determine the accountability and transparency of the procurement of fishing boats from the beginning of the procurement intended for community assistance and conformity to government procurement regulations. Accountability refers to the process of procuring fishing boats that have described responsibility for the management of APBN funds, while the transparency referred to is information disclosure to the public as a contributor to the state budget. Accountability and transparency can be realized if they comply with procedures and the existence of independent parties involved. The regulation in question is PP Nomor 16 Tahun 2018 concerning Government Procurement of Goods / Services and Government PP 27 Tahun 2014 concerning Management of BMN. The data sources used were interviews, observations and the presence of supporting documents such as the Berita Acara Serah Terima (BAST). The results of this study indicate that accountability and transparency have mostly been implemented and are in accordance with PP No. 16 Tahun 2018 and PP No. 27 Tahun 2014, however, the constraints of a lack of accountability occur from the external Ministry of Maritime Affairs and Fisheries. Realization of fisheries facilities assistance is not fully in accordance with the target, because there are still recipients who deliberately misuse their use.